Resting cerebral blood flow and ethnic differences in heart rate variability: links to self-reports of affect and affect regulation - Thayer, Julian F.; Koenig, Julian (NeuroImage, 2019)
Reduced high-frequency heart rate variability (HF-HRV) is associated with a greater risk for cardiovascular disease (CVD). Although African Americans (AA) are at greater risk for CVD, they show greater HF-HRV compared to European Americans (EA). Previous studies suggest that differences in the association between regional cerebral blood flow (CBF) and HF-HRV in AA and EA may explain this surprising pattern of findings, termed the Cardiovascular Conundrum. Here we pooled data from a total of n=452EA and n=102 AA, investigating differences in the association between CBF in 8 regions of interest (ROI), including the cingulate (anterior, mid, posterior), insula (anterior, posterior), and amygdala (basolateral, centromedial, superfical), with HF-HRV, mean heart rate (HR) and their Coefficient of Variation (CoV). Bayesian statistics illustrate that CBF - in particular in the anterior cingulate cortex (ACC) - is positively associated with HF-HRV and CoV in EA, but negatively associated in AA. Exploring the association between HF-HRV and CBF with self-reports of affect and affect regulation showed some differences as a function of ethnicity. The association between greater habitual use of reappraisal only showed a positive correlation with HF-HRV in AA. Similar, greater suppression or non-expression of angry emotions was associated with greater HF-HRV whereas greater outward direction of anger was associated with lower HF-HRV in AA only. Given the importance of the ACC in emotion and emotion regulation, we suggest that increased HF-HRV may serve a compensatory role in AA. Implications from these findings and suggestions for future studies are discussed.